Virtual Influencer Marketing: Examining the Impact of Perceived Authenticity and Source Attractiveness on Brand Trust with Digital Literacy as a Moderator - Pramana Putra, Made; Ferdianto, Jemmy Regri; Putra, Putu Yunartha Pradnyana; Padang, Rikky Rundu (Asosiasi Ahli Administrasi Indonesia, 2025)
The marketing landscape is witnessing a strategic shift from human to AI-powered virtual influencers (VIs). While their use is growing, their impact on brand trust remains unclear, especially concerning key attributes like perceived authenticity and source attractiveness, and how these are filtered by consumers' digital literacy. This quantitative study employed an online survey to collect data from 153 Indonesian social media users from Generations Y and Z who were actively exposed to VI content. Data were analyse using Structural Equation Modelling (SEM) with Partial Least Squares (PLS) to test hypotheses regarding the influence of perceived authenticity and source attractiveness on brand trust, with digital literacy as a moderating variable. The results confirmed that both perceived authenticity (β = 0.612, p < 0.001) and source attractiveness (β = 0.328, p < 0.001) have a significant positive effect on brand trust. Furthermore, digital literacy was found to be a significant, albeit weaker, moderating factor in this relationship (β = 0.167, p = 0.015), indicating that a consumer's level of digital sophistication influences how they process VI’s attributes to form brand trust. The study concludes that the effectiveness of VIs is not universal but is critically dependent on the audience's level of digital literacy. For theorists, this study extends models like the Elaboration Likelihood Model by validating their application to non-human entities. For managers, the findings underscore the need to prioritize authentic narrative-building and strategic VI alignment with brand identity.